The Life of Cuscuses (Phalangeridae): Action Plan Conservation Ex-situ - Farida, Wartika Rosa (Indonesian Cuscuses (Diprotodontia: Phalangeridae): Status and Perspective, 2022)
The use of wild animals for trading purposes has long been carried out physically, among others in the form of meat, skin and other body parts that have economic value, while aesthetically, such as for the attraction and maintenance of wild animals that show the physical beauty, sound and character of the species. The tendency to use wild animals, either directly or indirectly for economic reasons and pleasure, has put pressure and has an impact on the quality and quantity of wildlife populations in natural habitats. As a result of further pressure (over exploitation) that lasts for quite a long time and simultaneously has threatened the existence of several wildlife species in natural habitats. The threat to wildlife populations in the IUCN List of Red Book 2000 is divided into levels: Extinct (EX), Critically Endangered (CR), Endangered (EN), and Vulnerable (VU). In reality, over- harvesting/exploitation to utilize wild animals is still taking place more dominantly than conservation efforts. Therefore, aspects of the use and conservation of wild animals should consider proportionality, which will have a negative impact on the ecological balance and will cause damage to nature, which in turn will harm humans themselves.